2014
DOI: 10.1037/cfp0000008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on the association between subjective well-being and marital adjustment.

Abstract: This study was conducted to estimate the magnitude of genetic and environmental influences on the association between three indices of subjective well-being (i.e., life satisfaction, positive affect, negative affect) and positive and negative components of marital adjustment (i.e., spousal support, spousal strain) in a sample of adult married twin pairs (N = 453 pairs). Results indicated that subjective well-being and marital adjustment were significantly associated (particularly in women), that there were gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…The specific genetic factors explained about 81% of its total heredity, while the general genetic factor explained 19% of the heredity of the construct. Such findings were consistent with several results of the previous behavioral-genetic studies of the life satisfaction (Diener & Diener, 1996;Whisman et al, 2014). According to some researchers (Lykken & Tellegen, 1996;Pavot & Diener, 1993), gene-based basis of life satisfaction was to be found in more stable constructs, such as personality traits, which represented a more time-firing disposition than the life satisfaction itself, and determined its baseline level.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The specific genetic factors explained about 81% of its total heredity, while the general genetic factor explained 19% of the heredity of the construct. Such findings were consistent with several results of the previous behavioral-genetic studies of the life satisfaction (Diener & Diener, 1996;Whisman et al, 2014). According to some researchers (Lykken & Tellegen, 1996;Pavot & Diener, 1993), gene-based basis of life satisfaction was to be found in more stable constructs, such as personality traits, which represented a more time-firing disposition than the life satisfaction itself, and determined its baseline level.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, genes may have a qualitatively different form of influence on these constructs: protective or plastic (e.g., Belsky et al, 2009). The results of various behavioral-genetic studies suggest that the genetic contribution to life satisfaction varies from 25% to 55% (Diener & Diener, 1996;Whisman, Rhee, Hink, Boeldt, & Johnson, 2014). Moreover, results of a Dutch study regarding the life satisfaction report on a contribution of 38% to the genetic factors (Stubbe, Posthum, Boomsma, & De Geus, 2005), similar to the findings in Bartels (Bartels, 2015) meta-analysis.…”
Section: Behavioral Genetics Perspective Of Satisfaction With Life Anmentioning
confidence: 99%
“…One study found evidence for common genetic and nonshared environmental influences on the covariance between relationship quality and well-being, with evidence that partners were the source of the nonshared environmental influence [39]. In a study of male and female twin pairs and three indexes of well-being, the covariation between marital quality and well-being was largely due to genetic influences for women and genetic and non-shared environmental influences for men [40]. …”
Section: Findings From Studies Of Rge and Gxe And Relationship Outcomesmentioning
confidence: 99%